Realism and rhetoric in the evaluation of a new care model. Issue 3 (20th June 2019) - Grimwood, Tom
Abstract : Purpose: The purpose of this paper is to discuss the methodological challenges to evaluating one of the 50 vanguard sites of the new care model (NCM) programme for integrated care in England, and make the case for a modified realist approach to this kind of evaluation. Design/methodology/approach: The paper considers three challenges to evaluating the NCM in this particular vanguard: complexity, strategy and rhetoric. It reflects on how the realist approach negotiates these philosophical challenges to delivering integrated care, in order to provide contextualised accounts of who a programme works for, in what context, and why. Findings: The paper argues that, in the case of this particular vanguard site, the tangible benefit of the realist approach was not in providing a firm epistemological basis for evaluation, but rather in drawing out and articulating the ontological rhetoric of such large-scale transformation programmes. By understanding the work of the NCM less as an objective "system", and more as a dynamic form of persuasion, aimed at securing the "adherence of minds" (Perelman and Olbrechts-Tyteca, 2008, p. 8) in multiple audiences, the paper suggests that realist evaluation can be used to address both the systematic issues and localised successes the NCMs encountered. Originality/value: The paper identifies a number of aspects of new models of integrated care for evaluators to consider. It offers ways of negotiating the challenges to conventional outcome-focused evaluation, by drawing attention to the need for contextualised, time-situated and audience-sensitive value of NCMs.